Inside Health Care : Neonatal Intensive Care - Who Decides? Who Pays? Who Can Afford It? - Mathew, Oommen P., 1948- (Bentham Science Publishers, 2013)
Health care in the US is facing a crisis, but there is polarization and disagreement among policy makers and the public about how to solve this crisis. The overall outcome is ranked much lower than most developed nations and nearly 50 million people are uninsured. Health care is big business and is 17 % of the gross domestic product. Inside Health Care highlights the lifesaving nature of neonatal care while shining some light on what can be done to maximize neonatal well being and efficiency in healthcare access and delivery. In this book, health care issues are brought under the lens by physi.